The State of Governance Bangladesh 2014-2015: institutions, outcomes, accountability - Rahman, Sultan Hafeez; Ahmed, Kazi Niaz; Aziz, Syeda Salina; Mannan, Sadiat; Rahman, Muhammad Ashikur; Rashid, Md. Harun-Or-; Razzaque, Farhana; Uddin, Mohammed Misbah; Zillur, Kaneta (BRAC University, 2018)
Includes bibliographical references (page 174 - 160).